Evaluating Costs of Biologic Drugs for the Treatment of Moderate-to-Severe Psoriasis in the United States. Issue 3 (July 2019) - Feldman, Steven R.; Wu, Jashin J.; Armstrong, April W.; Lebwohl, Mark; Jacobson, Abby A.; Lingohr-Smith, Melissa; Lin, Jay
Objective: To provide a contemporary comparative assessment of biologic drug costs and cost effectiveness for treating moderate-to-severe psoriasis in the United States. Methods: A literature search was conducted in PubMed on October 4, 2018 with the search terms of "psoriasis, " "biologic, " and "cost" with a filter of publication dates within the last 5 years (2014-2018). Studies included in this review were required to be conducted from a United States perspective. Results: Of the 16 studies retrieved, the costs associated with use of biologic drugs for the treatment of moderate-to-severe psoriasis were relatively high, with some drugs exhibiting sustained lower costs than others. Some comparative findings on the cost-effectiveness of biologic drugs based on the annual treatment cost per Psoriasis Area and Severity Index (PASI) 75 responder concluded that the annual treatment cost was lowest for brodalumab 210 mg at US48 782; the cost was highest for ustekinumab 45/90 mg (US87 243), followed by adalimumab 40 mg (US82 655), ixekizumab 160 mg (US77 957), and secukinumab 300 mg (US75 671). The annual treatment cost per PASI 100 responder was also lowest for brodalumab at US87 585. This pattern remained consistent in other cost studies, with brodalumab being the treatment with the lowest treatment costs when compared to other biologic drugs. Conclusion: Brodalumab was consistently observed to be the least costly treatment option among biologic drugs used to treat moderate-to-severe psoriasis in the United States, which is largely the result of its low-drug cost and high-PASI response rate.